25 years of BIISS : an anthology - Abdul Mubeen, Md.; Kabir, Mohammad Humayun; Bangladesh Institute of International and Strategic Studies (Dhaka : Academic Press and Publishers in association with Bangladesh Institute of International and Strategic Studies, 2003)
Excerpts of articles from BIISS journal on topic dealing with security in South Asia in perspective and Bangladesh national security in general.
Includes bibliographical references.
Keywords: World politics -- 1945-1989.